Coastal Sea Levels, Impacts and Adaptation - Ivan Haigh (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Extreme sea levels can lead to hazardous events, such as coastal flooding, erosion, or salt water intrusion, with-wide ranging environmental, societal, and economic consequences. In combination with climate-driven sea-level rise, and, potentially, additional changes in storminess, dynamic wave contributions, and tidal dynamics, the adverse consequences of extreme oceanographic events are expected to escalate in many regions. Integrated coastal zone impact assessments can guide the decisions on the adaptive responses to these changes in the physical environment and for the socioeconomic development of the local communities.